A274 EARLY SINGLE-OPERATOR CHOLANGIOSCOPY ASSISTED ELECTROHYDRAULIC LITHOTRIPSY (SOC-EHL) IN THE MANAGEMENT OF DIFFICULT BILIARY STONES IS COST-EFFECTIVE WHEN COMPARED TO A DELAYED STEP-UP APPROACH TO LATER SOC-EHL. (26th February 2020) - Alrajhi, S; Barkun, A N; Adam, V; Callichurn, K; Martel, M; Brewer, O; Khashab, M; Forbes, N; Chen, Y
Abstract: Background: Single-operator cholangioscopy assisted electrohydraulic lithotripsy is the standard of care for difficult common bile duct (CBD) stones with failed clearance using standard ERCP. This technology is expensive and optimal timing of its use in terms of cost-effectiveness in the management algorithm of patients with difficult CBD stones remains unclear Aims: To determine the cost-effective timing of SOC-EHL utilization in the management of difficult CBD stones Methods: A decision model was developed assessing 4 strategies and progressively delayed introduction of SOC-EHL in relation to ERCP over 6-months. Difficult stones were defined as having failed CBD clearance via standard ERCP. Probability estimates for each health state were obtained from a literature systematic review. For each strategy, outpatients undergoing ERCP underwent different timings of SOC-EHL introduction from the first to the fourth ERCP and were followed for subsequent need for re-intervention, adverse events, need for surgery, and/or successful endoscopic CBD clearance. The unit of effectiveness was complete CBD clearance without need for surgery. Deterministic sensitivity analyses were performed varying all 50 model variables across ranges spanning 30% of their respective values. Costs are in 2018US based on US data. Results: Performing SOC-EHL immediately during the first ERCP is the least expensive approach when compared to delaying SOC-EHL. This strategy costs 15, 528 on average per patient with CBD clearance avoiding surgery and can save between 260 to 720 compared to the 3 other strategies, which introduce SOC-EHL during the second to the fourth ERCP. Effectiveness is clinically comparable between the four strategies ranging from 97–99%. Deterministic sensitivity analysis shows changes in the results when the ERCP complication rate (baseline probability of 6%) decreases to 4.5%, when the SOC-EHL (baseline costs of 2, 450) costs more than 2, 670, or when the ERCP facility fees (baseline costs of 4, 292) are less than 3, 425. In all 3 scenarios, delaying the first SOC-EHL use to the fourth procedural attempt becomes the dominant strategy. Variations of the other 47 variables did not alter results. Conclusions: Although SOC-EHL is expensive, this analysis demonstrates that among patients who have failed a prior attempt at stone extraction, utilization of SOC-EHL at the next (first subsequent) ERCP is less costly when compared to its delayed introduction. However, postponing the use of SOC-EHL to the fourth ERCP could be identified as the most cost-effective strategy when facility fees or ERCP complications rates are below certain thresholds, or when the costs of SOC-EHL extend beyond a defined threshold. Funding Agencies: None